2007
DOI: 10.1177/1471301207080364
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental change on residents with dementia

Abstract: This qualitative study aimed to identify and describe the relatives' and staff's perceptions of environmental change on residents with dementia. Data were collected from audio-taped relative and staff focus group interviews at an aged care facility in Western Sydney. The transcribed data from the focus groups were thematically analysed and categorized. Three major categories emerged from the analysed data: the special care unit as a family home, therapeutic environment and work environment. Relatives and staff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Past research has demonstrated that enhancing the environment, whether through introduction of activities or animal therapy, has a positive impact on residents in long-term care facilities 35,36 ; however, the physical benefits of an exercise program has not been previously demonstrated in this population. In short, future work is needed to dissect the components of the exercise program to determine which are effective in reducing negative affect in residents of a secured dementia unit.…”
Section: Limitationsmentioning
confidence: 97%
“…Past research has demonstrated that enhancing the environment, whether through introduction of activities or animal therapy, has a positive impact on residents in long-term care facilities 35,36 ; however, the physical benefits of an exercise program has not been previously demonstrated in this population. In short, future work is needed to dissect the components of the exercise program to determine which are effective in reducing negative affect in residents of a secured dementia unit.…”
Section: Limitationsmentioning
confidence: 97%
“…This approach to staffing within the households aimed to enhance familiarity among residents, families and staff. While this concept of smaller, self-contained, more home-like environments had been examined in other contexts (Cioffi et al 2007;Lum et al 2008;Schwarz et al 2004), empirical evidence in the Canadian and more specifically, Nova Scotian long-term care context was limited. A nationally funded research team sought to address this paucity through its research examining the impact of different models of care on resident quality of life.…”
Section: Messages-clémentioning
confidence: 99%
“…The investment the province intended to make in long-term care necessitated study of other jurisdictions, nationally and internationally, for best practice. Evidence pointed to the benefits of a more home-like environment with private rooms, decentralized bathrooms, dining and leisure spaces (Schwarz et al 2004;Cioffi et al 2007;Lum et al 2008) 1 -which led the province to adopt the household model as a requirement for owners/operators seeking to build government-funded new and replacement nursing homes.…”
Section: History and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In the realm of physical and social environmental effects on people with dementia, there were published studies such as: 1) the research by Cloffi, Fleming, Wilkes, Sinfield, and Le Mlere (2007) where through conducting focus groups with families and staff, researchers were able to document positive changes in behavior and functioning of residents in a special care unit when smaller more home-like units were initiated; 2) Van Hoof's and Kort's (2009) concept paper on designing a dementia friendly home in terms of architectural features, interior design, the indoor environment, and technological assistive devices all to facilitate people with dementia to remain independent and in their own homes as long as possible; and 3) Davis, Byers, Nay, and Koch (2009), who in their article argued that it is the lived experience of people with dementia that should guide the building of residential facilities suggesting seven living experiences to be considered in architectural design: eating, bedroom, family and community connections, personal enjoyment, staff, and end-of -life experiences.…”
mentioning
confidence: 99%